Cost-Effectiveness Analysis of Fourth- or Further-Line Ripretinib in Advanced Gastrointestinal Stromal Tumors - Liao, Weiting; Xu, Huiqiong; Hutton, David; Wu, Qiuji; Zhou, Kexun; Luo, Hui; Lei, Wanting; Feng, Mingyang; Yang, Yang; Wen, Feng; Li, Qiu (Frontiers in Oncology, 2021)
BACKGROUND: The INVICTUS trial assessed the efficacy and safety of ripretinib compared with placebo in the management of advanced gastrointestinal stromal tumors. METHOD: We used a Markov model with three health states: progression-free disease, progression disease and death. We parameterized the model from time-to-event data (progression-free survival, overall survival) of ripretinib and placebo arms in the INVICTUS trial and extrapolated to a patient’s lifetime horizon. Estimates of health state utilities and costs were based on clinical trial data and the published literature. The outcomes of this model were measured in quality-adjusted life years (QALYs), costs, and incremental cost-effectiveness ratios (ICERs). Uncertainty was tested via univariate and probabilistic sensitivity analyses. RESULTS: The base-case model projected improved outcomes (by 0.23 QALYs) and additional costs (by 63,779) and yielded an ICER of 281,251/QALY gained for ripretinib versus placebo. The results were most sensitive to progression rates, the price of ripretinib, and health state utilities. The ICER was most sensitive to overall survival. When overall survival in the placebo group was lower, the ICER dropped to 115,210/QALY. The ICER dropped to 150,000/QALY when the monthly cost of ripretinib decreased to 16,000. Probabilistic sensitivity analyses revealed that ripretinib was the cost-effective therapy in 42.2% of simulations at the willingness-to-pay (WTP) threshold of 150,000/QALY. CONCLUSION: As the fourth- or further-line therapy in advanced gastrointestinal stromal tumors, ripretinib is not cost-effective in the US. Ripretinib would achieve its cost-effectiveness with a price discount of 50% given the present effectiveness.